Tradisi Integrasi Ilmu dalam Institusi Pendidikan Islam - Abidin, Zainal (Khazanah: Jurnal Studi Islam dan Humaniora, 2014)
The Integration of secience in Islamic tradition is importance aspect. In the Islamic historical contect indicated that Islamic education was supported to integration of secience, because more of islamic educa- tion institution can be important playing in developing aspect especially to built the civiulization araound the world. From early Islam period, many institution of Islamic education was produced several Islamic intellectuals heritage and more Islamic scholars, so its developed sciences of Islamic perspectives. This tradition is a branch of muslim identity who has influenced for many ages. After Islam be came the ones of gread religion in the world,its tradition was established and until now the influence of Islamic tradition in scientific method must be developed and be come to the great interests between Islamic scholars in many Islamic countries.